Socio-demographic determinants of timely adherence to BCG, Penta3, measles, and complete vaccination schedule in Burkina Faso - Schoeps, Anja; Ouédraogo, Nobila; Kagoné, Moubassira; Sié, Ali; Müller, Olaf; Becher, Heiko (Vaccine, 2013)
Objective - To identify the determinants of timely vaccination among young children in the North-West of Burkina Faso. - Methods - This study included 1665 children between 12 and 23 months of age from the Nouna Health and Demographic Surveillance System, born between September 2006 and December 2008. The effect of socio-demographic variables on timely adherence to the complete vaccination schedule was studied in multivariable ordinal logistic regression with 3 distinct endpoints: (i) complete timely adherence, (ii) failure, and (iii) missing vaccination. Three secondary endpoints were timely vaccination with BCG, Penta3, and measles, which were studied with standard multivariable logistic regression. - Results - Mothers’ education, socio-economic status, season of birth, and area of residence were significantly associated with failure of timely adherence to the complete vaccination schedule. Year of birth, ethnicity, and the number of siblings was significantly related to timely vaccination with Penta3 but not with BCG or measles vaccination. Children living in rural areas were more likely to fail timely vaccination with BCG than urban children (OR=1.79, 95%CI=1.24-2.58 (proximity to health facility), OR=3.02, 95%CI=2.18-4.19 (long distance to health facility)). In contrast, when looking at Penta3 and measles vaccination, children living in rural areas were far less likely to have failed timely vaccinations than urban children. Mother's education positively influenced timely adherence to the vaccination schedule (OR=1.42, 95%CI 1.06-1.89). There was no effect of household size or the age of the mother. - Conclusions - Additional health facilities and encouragement of women to give birth in these facilities could improve timely vaccination with BCG. Rural children had an advantage over the urban children in timely vaccination, which is probably attributable to outreach vaccination teams amongst other factors. As urban children rely on their mothers’ own initiative to get vaccinated, urban mothers should be encouraged more strongly to get their children vaccinated in time.